Intervertebral disc kinematics in active duty Marines with and without lumbar spine pathology - Keenan Onodera; David B. Berry; Bahar Shahidi; Karen R. Kelly; Samuel R. Ward (JOR Spine, 2019)
Abstract Military members are required to carry heavy loads frequently during training and active duty combat. We investigated if operationally relevant axial loads affect lumbar disc kinematics in forty‐one male active duty Marines with no previous clinically diagnosed pathology. Marines were imaged standing upright with and without load. From T2‐weighted magnetic resonance images, intervertebral disc (IVD) health and kinematic changes between loading conditions and across lumbar levels were evaluated using two‐way repeated measures analysis of variance tests. IVD kinematics with loading were compared between individuals with and without signs of degeneration on imaging. Linear regression analyses were performed to determine associations between IVD position and kinematic changes with loading. Fifty‐eight percent (118/205) of IVDs showed evidence of degeneration and 3% (7/205) demonstrated a disc bulge. IVD degeneration was not related to posterior annular position (P > .205). Changes in sagittal intervertebral angle were not associated with changes in posterior annular position between baseline and loaded conditions at any lumbar level (r < 0.267; P = .091‐.746). Intervertebral angles were significantly larger in the lower regions of the spine (P < .001), indicating increased local lordosis when moving in the caudal direction Disc height at the L5/S1 level was significantly smaller (6.3 mm, mean difference = 1.20) than all other levels (P < .001) and baseline posterior disc heights tended to be larger at baseline (7.43 mm ± 1.46) than after loading (7.18 ± 1.57, P = .071). Individuals with a larger baseline posterior annular position demonstrated greater reduction with load at all levels (P < .002), with the largest reductions at L5/S1 level. Overall, while this population demonstrated some signs of disc degeneration, operationally relevant loading did not significantly affect disc kinematics.